International perspectives on the governance of higher education [ alternative frameworks for coordination - Huisman, Jeroen (International studies in higher education, 2009)
Essential reading for policy makers, institutional leaders, managers, advisors, and scholars in the field of higher education, The Governance of Higher Education analyzes how higher education systems of governance have evolved in recent years. An authoritative overview that questions why some systems of governance have persisted while others have experienced patterns of change, it further looks at how governments shape the policy-making process in higher education in an effort to secure particular policy outcomes